Effects of magnetohydrodynamic unsteady fluid flow over a narrow channel in the axial and radial directions. Issue 1 (31st December 2022) - Ganesh, S.; Anand, V.W.J.; Chandrasekar, P.; Anish, M.
Abstract : The study of flow of fluid in a porous channel in a stenosis with the influence of an unsteady magnetic field, which is uniform, is considered. The mathematical formulation of this problem is considered to be very consistent along with the principles of magnetohydrodynamics (MHD). Blood is usually taken as a Homogenous Newtonian fluid and is treated as a magnetic fluid with electrical conductivity. The Finite Volume (FV) method in curvilinear coordinates is generally used for the discretisation of the system of equations which governs the MHD fluid flow. Numerical solution of this problem, which is described by coupled nonlinear partial differential equation, with required BCs is solved by using MATLAB. Results related to velocity, pressure and skin friction in this paper show the presence of the magnetic field which in turn influences the flow field.